How Western European Nuclear Policy is Made - Muller, Harald. author. aut Link
XIV, 241 p.
Keywords: Second in a series of comparative studies on West European non-proliferation policy, this book examines the factors which influence policy in this area, and assesses the potential for policy convergence in the future. With a multi-national team of contributors, this study covers 10 countries.